Drag Reduction by Natural Polymeric Additives in PMDS Microchannel: Effect of Types of Additives - Fiona Ling, Wang Ming; Abdulbari, Hayder A. (EDP Sciences, 2017)
Drag reduction technology was used in medical applications to enhance the blood flow in semiclogged blood streams which can be an alternative treatment for atherosclerosis. In this present study, natural polymeric drag reducing additives (DRA) was introduced to replace synthetic polymer which has the possibility of bringing side effects to human health. Three different sources, namely okra, aloe vera and hibiscus were utilized to extract the natural polymeric additives which were then tested in custom made microchannel simulating human heart blood vessels. The performance of different types of additives was evaluated using pressure measurements. The maximum drag reduction up to 63.48% is achieved using 300 ppm of hibiscus mucilage at operating pressure of 50 mbar. In this present work, hibiscus showed the best drag reduction performance, giving the highest %FI in most of the cases. This experimental results proved that these natural polymeric additives could be utilized as DRA in enhancing the blood flow in semiclogged blood streams.